Structural Empowerment, Resilience, and Intent to Stay Among Nurses and Midwives in Obstetrics and Gynecology Departments: A Phenomenological Inquiry Study in Saudi Arabia - Areej Ghalib Al-Otaibi RN, PhD; Ahmad E. Aboshaiqah RN, PhD; Fatimah Ali Aburshaid MSc (SAGE Publishing, 2024)
Introduction Staff turnover is a major obstacle to the success of Saudi Arabia's health transformation agenda and the realization of Saudi Vision 2030. Nurses' and midwives' intentions to remain with the organization are heavily influenced by their sense of structural empowerment and resilience. Objectives To gain insight into the perspectives of nurses and midwives working in the Obstetrics and Gynecology departments of a selection of Saudi Arabian governmental hospitals about structural empowerment, resilience, and intentions to stay in their current positions. Methods Qualitative Descriptive Phenomenology. Purposive sampling was used to choose eighteen nurses and midwives working in the OB/GYN department in three government hospitals in the Eastern Province of Saudi Arabia. Semi-structured interviews were conducted to gather the participants' perceptions. Colaizzi's steps were used as a data analysis method. Results The narratives of the selected participants generated five major themes: (a) "nurturing physical and physiological," (b) "developing psychological," (c) "managing financial," (e) "restructuring organizational," and (f) "enriching professional and occupational." Conclusions The emerging major themes highlighted the perceptive elements of nurses and midwives that keep them empowered, resilient, and determined to stay in their organization. A failure to fulfill any one of these elements will affect the others. To improve organizational outcomes, empowerment and resilience must be obtained.